1993
DOI: 10.1007/bf01741166
|View full text |Cite
|
Sign up to set email alerts
|

Induction of delayed-type hypersensitivity responses by monoclonal anti-idiotypic antibodies to tumor cells expressing carcinoembryonic antigen and tumor-associated glycoprotein-72

Abstract: The use of anti-idiotypic antibodies as immunogens represents one potential approach to active specific immunotherapy of cancer. Two panels of syngeneic monoclonal anti-idiotypic antibodies were generated. One panel was directed against mAb CC49 and the other to mAb COL-1. mAb CC49 recognizes the pancarcinoma antigen (Ag), tumor-associated glycoprotein-72 (TAG-72), and mAb COL-1 recognizes carcinoembryonic antigen (CEA). Seven anti-idiotypic (AI) antibodies (Ab2) designated AI49-1-7 were generated that recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Such Ab2 preparations may have high potential of eliciting specific humoral immunity in cancer patients. Like monoclonal Ab2 FG1 described here, a few of those Ab2s also elicited specific DTH reactions after challenge with antigen-positive tumor cells in experimental animals (Austin et al, 1991;Chen et al, 1991;Pohl et al, 1992;Irvine and Schlom, 1993;Mansoor et al, 1993). However, in each of those studies, human tumor cells expressing the relevant antigen were used for challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Such Ab2 preparations may have high potential of eliciting specific humoral immunity in cancer patients. Like monoclonal Ab2 FG1 described here, a few of those Ab2s also elicited specific DTH reactions after challenge with antigen-positive tumor cells in experimental animals (Austin et al, 1991;Chen et al, 1991;Pohl et al, 1992;Irvine and Schlom, 1993;Mansoor et al, 1993). However, in each of those studies, human tumor cells expressing the relevant antigen were used for challenge.…”
Section: Discussionmentioning
confidence: 99%
“…T cell immunity against anti-id MAbs against anti-CEA MAbs have also been re ported [4,12,14]. Durrant et al [4] demon strated that tumor-infiltrating lymphocytes obtained from colon cancer patients and stim ulated in vitro with anti-id MAbs proliferated in response to purified CEA.…”
Section: Application Of Anti-id Mab For Tumor Immunotherapymentioning
confidence: 99%
“…How ever, Irvine and Schlom [12] have recently reported that anti-id MAb against anti-carbo hydrate antigen TAG72 MAb could induce a DTH response in BALB/c mice. MacLean et al [13] have observed a DTH reaction at the subcutaneous vaccination site to the synthetic form of the immunodominant disaccharide ((3-Gal-3 GalNAc) of the Thomsen-Friedenreich antigen conjugated to KLH in patients with ovarian cancer.…”
Section: Application Of Anti-id Mab For Tumor Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas an Ab2P generated against an anti-CEA monoclonal antibody that recognizes a CEA-specific epitope, would be theoretically safer and more effective. Furthermore, Ab2fl expressed in a different molecular environment have been shown to overcome the immunosuppression in the host by stimulating "silent clones," and/or allowing (19)(20)(21)(22)(23)(24)(25)(26)(27). We have generated and characterized an anti-idiotype murine monoclonal antibody to a murine monoclonal antibody designated 8019 that identifies a specific epitope on CEA (28).…”
Section: Introductionmentioning
confidence: 99%